If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2/5)=(1/4)+f
We simplify the equation to the form, which is simple to understand
(2/5)=(1/4)+f
Simplifying:
( + 0.4)=(1/4)+f
Simplifying:
( + 0.4)=( + 0.25)+f
Remove unnecessary parentheses
+ 0.4=( + 0.25)+f
Remove unnecessary parentheses
+ 0.4=0.25+f
We move all terms containing f to the left and all other terms to the right.
-1f=0.25-0.4
We simplify left and right side of the equation.
-1f=-0.15
We divide both sides of the equation by -01 to get f.
f=0.15
| 5g+3(-8+2g)=1-g | | 4m+3n=8 | | 3x-7x=44 | | x+5(x+6)+25-12(x-12+5)3x+2x-3y+56.25=25 | | (4/5)=(1/4)+f | | 6g+3(-6+4g)=1-g | | (14/4)y+(2/2)=3y-4 | | -4(x+1)-32=3x-7(x+6) | | -8-14+5b=11 | | -31-(4x)=-5-5(1+5x) | | (x/2)-6=(x/5)-3 | | x+(12/8)=(3/4)x | | x/15=3/5 | | x+(7/8)=2x-(7/8) | | 3(x-5)+10=5x | | x+5(x+6)+25-12(x-12+5)=25 | | 0.5x+3=x^2 | | x/3+2=8 | | 2(x+4)/5=3x-1 | | 4x+3(x-2)=71 | | 560=(x+10)(x+22)-(x+12)(x) | | X^7-64x=0 | | (2/7)x+(1/7)=-(5/7) | | -7x+4x(3x-5)=-9-6x | | 7x-12-6x=5 | | 7x+14-3x=2(2x+7) | | 7.7r+6=6.7r+6 | | 28-12x=28-14x | | -3x-(7/3)=(29/3) | | 7.7r+6=6.7y+6 | | x^3-x^2-50x+50=0 | | 4n+40=7(-2n+2) |